2015
DOI: 10.3892/mmr.2015.3273
|View full text |Cite
|
Sign up to set email alerts
|

Association of hsa-miR-145 overexpression in human testicular cells with male infertility

Abstract: MicroRNAs (miRs) have crucial functions in spermatogenesis and implications for male infertility. In the present study, Homo sapiens (hsa)‑miR‑145 was designed and cloned into the eukaryotic expression plasmid pGenesil‑1. The recombinant plasmids were transfected into Hs 1.tes normal testicular cells and NTERA‑2 testicular cancer cells. Quantitative polymerase chain reaction of hsa‑miR‑145 indicated that pGenesil‑1‑miR‑145 effectively upregulated the expression of hsa‑miR‑145 in vitro. hsa‑miR‑145 overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…determined that miR-23b , miR-32 , miR-154 and miR-99 in MArrest and SCOS were up-regulated 42 , and we found that these genes were also up-regulated in NOA. SOX9 is an essential protein for the maturation of sertoli cells and normal spermatogenesis, and it is a possible target of miR-145 43 , 44 . Furthermore, we observed that mir-145 is one of the common up-regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…determined that miR-23b , miR-32 , miR-154 and miR-99 in MArrest and SCOS were up-regulated 42 , and we found that these genes were also up-regulated in NOA. SOX9 is an essential protein for the maturation of sertoli cells and normal spermatogenesis, and it is a possible target of miR-145 43 , 44 . Furthermore, we observed that mir-145 is one of the common up-regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although miRNAs are reported to regulate bone forming and resorption cells activities (58), circulating miRNA specific to bone metabolism has not been identified, owing to the diverse biologic roles and tissue distribution of miRNAs. As miR-145 has been detected in tissues other than bone, including human testicular cells and smooth muscle cells (59,60), it is reasonable to speculate that the circulating level of miR-145 is not solely related to bone metabolic status normal physiologic conditions. In this study, the negative correlation between circulating miR-145 and some bone turnover markers in AIS suggests that the abnormal systemic change of miR-145 in AIS osteoblasts and osteocytes may abrogate the physiologic profile of circulating miR-145 and other bone markers, therefore, leading to the unique correlation profile in AIS (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that overexpression of miR-145 downregulates expression of male sex-determining gene SOX9 that in turn induces male fertility. Therefore the oncogenic role of miR-145 reveals its diagnostics and prognostic value as an infertility bio-marker [51]. miR-1471 was found to be overexpressed in patients with sertoli-cell-only syndrome that is characterized by azoospermia therefore miR-1471 can be used as a promising strategy against male infertility [52].…”
Section: • Vol 17 • № 5 Obstetrics Gynecology and Reproductionmentioning
confidence: 99%